New Insights into Bone Loss in RA - Andreev, Darja; Bozec, Aline (Osteologie, 2021)
The negative impact of rheumatoid arthritis (RA) on bone mineral density is well characterized. Notably, articular bone erosion is a central feature of RA, leading to joint damage and disabilities. In addition, the axial and appendicular skeleton can be affected, which secondly manifests in bone fracture. The main trigger of RA-associated bone loss is excessive bone degradation by osteoclasts and impaired bone formation by osteoblasts. In particular, the inflammatory status, reflected by high level of proinflammatory cytokines, receptor activator of nuclear factor κB ligand (RANKL), and autoantibodies induces the formation of bone-resorbing osteoclasts. Today, antirheumatic therapy effectively hampers synovial inflammation and bone erosion. However, current medication is unable to repair established bone lesions. This review outlines the knowledge gained about the pathophysiology of rheumatoid arthritis and the molecular mechanisms that promote osteoclast-mediated bone erosion and inhibit osteoblast-related bone formation, pointing out possible new intervention for inflammatory bone disease.
Keywords: Rheumatoid arthritis; bone erosion; Osteoclasts; Osteoblasts